“Believe a friend? He is a man. /He has the essence of falseness”. Masculinity in the works of Francília (Francisca Paula Possolo da Costa) and Sóror Dolores (Maria da Felicidade de Couto Browne) - Biguelini, Elen (História: Questões e Debates, 2018)
Based on literary criticism and women’s history, this text has the interdisciplinary objective of understanding women’s position within Portuguese XIX century society. It will be done through the analyses of how Francisca Paula Possolo da Costa and Maria da Felicidade de Couto Brown related to masculinity within their poetry. Francília (Francisca Possolo) and Sóror Dolores (Sister Pain, Maria Browne) were two Portuguese poets who wrote about male ‘betrayal’. They were deceived by men they loved, and their work shows this betrayal changed their writing and lived their lives. In this paper, it is intended to analyze the work of both Portuguese authoresses (one from Lisbon, the other from Porto) with the purpose of understanding their opinions regarding masculinity and the image created by them of their contemporary men.